Eastern Wines on Western Tables : Consumption, Trade and Economy in Ancient Italy - Komar, Paulina, (Mnemosyne, Supplements ;, 2021)
Eastern Wines on Western Tables: Consumption, Trade and Economy in Ancient Italy is an interdisciplinary and multifaceted study concerning wine commerce and the Roman economy during Classical antiquity. Wine was one of the main consumption goods in the Mediterranean during antiquity, and the average Roman adult male probably consumed between 0,5 - 1 litre of it per day. It is therefore clear that the production and trading of wine was essential for the Roman economy. This book demonstrates that wines from the Eastern Mediterranean and the Aegean region in particular, played a crucial part in wine commerce. Moreover, it sheds new light on economic dilemmas that have long puzzled scholars, such as growth and market integration during antiquity.